ICT-Based Tafsir PAI Learning and Its Implications for Class XA Santri Learning Interests at MA Muwahidun Pati - Nur Farid Khoiruddin; Hafidz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to examine the implementation of Islamic Religious Education (PAI) Tafsir learning based on Information and Communication Technology (ICT) and its implications for the learning interests of class XA students at Madrasah Aliyah (MA) Muwahidun Pati. The research method used is descriptive qualitative with a case study approach. Data were obtained through observation, interviews, and documentation. The research results show that the use of ICT in learning PAI Tafsir can significantly increase students' interest in learning. Students become more active and motivated in participating in learning, and find it easier to understand the material presented. ICT-based learning also provides an interesting and interactive variety of teaching methods, creating a fun learning atmosphere. The implications of this research show that the integration of ICT in learning PAI Tafsir can be an effective strategy in improving the quality of religious education at MA Muwahidun Pati. In addition, this research suggests that teachers use ICT more in the learning process to maximize the potential of technology in the world of education.